Application of spike sorting algorithm to neuronal signals originated from boron doped diamond micro-electrode arrays - Klempíř, O; Krupička, R; Krůšek, J; Dittert, I; Petráková, V; Petrák, V; Taylor, A (Physiological research, 2020)
In this work we report on the implementation of methods for data processing signals from microelectrode arrays (MEA) and the application of these methods for signals originated from two types of MEAs to detect putative neurons and sort them into subpopulations. We recorded electrical signals from firing neurons using titanium nitride (TiN) and boron doped diamond (BDD) MEAs. In previous research, we have shown that these methods have the capacity to detect neurons using commercially-available TiN-MEAs. We have managed to cultivate and record hippocampal neurons for the first time using a newly developed custom-made multichannel BDD-MEA with 20 recording sites. We have analysed the signals with the algorithms developed and employed them to inspect firing bursts and enable spike sorting. We did not observe any significant difference between BDD- and TiN-MEAs over the parameters, which estimated spike shape variability per each detected neuron. This result supports the hypothesis that we have detected real neurons, rather than noise, in the BDD-MEA signal. BDD materials with suitable mechanical, electrical and biocompatibility properties have a large potential in novel therapies for treatments of neural pathologies, such as deep brain stimulation in Parkinson's disease.
Keywords: mikroelektrody; Algorithms; akční potenciály; krysa rodu Rattus; Hippocampus; zvířata; Action Potentials; neurony; hipokampus; titan; potkani Wistar; Microelectrodes; Titanium; Rats, Wistar; Diamond; Male; Boron; Neurons; algoritmy; diamant; Rats; Animals; mužské pohlaví; bor